Preparation of Glycoside Compounds Containing of Different Cyclic Substituent’s - et.al, Nabel Abed Abed Al-Radha (Al-Qadisiyah Journal of Pure Science, 2017)
The aromatic Schiff base compounds were characterized with their activity against different types of bacteria, Fungi, Viruses and as cancer diseases. However, most of these compounds are characterized by low solubility in biological systems. In this study the preparation of new derivatives carbohydrates are characterized by there association with homogenous and heterogeneous cycles by azo methine group (C=N) , as well as the preparation of new carbohydrates derivatives characterized by the attachment of monosaccharide by the same group or by the tetrazole ring . The first stage is the preparation of sugar derivatives of fructose . The second stage is the preparation of carbohydrates derivative characterized by the attachment of two monosaccharide with tetrazole ring. The structures of the products obtained have been identified by spectral (IR , H1-NMR) , elemental (C,H,N) analyses and by some physical properties